Chemically functionalized silica gel with alkynyl terminated monolayers as an efficient new material for removal of mercury ions from water - Choi, Jae Min; Jeong, Daham; Cho, Eunae; Jun, Bong-Hyun; Park, Seyeon; Yu, Jae-Hyuk; Tahir, M. Nazir; Jung, Seunho (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
•Silica gel surface was successfully functionalized with alkynyl monolayers.•The modified surface was characterized by XPS, ATR-IR and elemental analysis.•The functionalized surface was evaluated as a novel adsorbent for mercury removal.•The maximum adsorption capacity was 171.48mg of Hg2+ per gram of adsorbent. An efficient new material for removal of mercury from water was prepared by the chemically functionalization of silica gel. Various monolayers were grafted on the silica gel surface to attach terminal alkynyl groups. All modified surfaces were characterized by XPS, ATR-IR and elemental analysis while Hg2+ concentrations were determined by ICP-OES. The Hg2+ adsorption reached equilibrium within 2h with maximum adsorption capacities of 174.3mgg−1 for alkynyl monolayers functionalized silica gel. Due to relatively lower price of silica gel, it can be efficiently used after functionalization on large scale to remove Hg2+ ions from the wastewater.